2012
DOI: 10.1002/bit.24429
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface charge property on Escherichia coli initial adhesion and subsequent biofilm formation

Abstract: Polyethylene (PE) sheets were modified by radiation-induced graft polymerization (RIGP) of an epoxy-group containing monomer glycidyl methacrylate (GMA). The epoxy group of GMA was opened by introducing sodium sulfite (SS) and diethylamine (DEA) as representatives of negatively and positively charged functional groups, respectively. These modified surfaces by RIGP, termed GMA, SS, and DEA sheets, were investigated to elucidate their effects on initial adhesion and subsequent biofilm formation of Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 61 publications
3
62
0
Order By: Relevance
“…Terada et al [75] showed that the surface charge is very important not only during initial cell adhesion but also in the long term biofouling formation of E. coli cells onto polymeric surfaces.…”
Section: Membrane Surface Chargementioning
confidence: 99%
“…Terada et al [75] showed that the surface charge is very important not only during initial cell adhesion but also in the long term biofouling formation of E. coli cells onto polymeric surfaces.…”
Section: Membrane Surface Chargementioning
confidence: 99%
“…Surface charge is of vital importance in a diverse range of complex interfacial systems, though perhaps most significantly in living systems, where it is known to play a key role in many processes, including cellular growth and division [102,103], adherence [104][105][106], cellular uptake [107][108][109][110][111] and communication [112][113][114]. Thus, a robust method of quantitatively resolving spatial heterogeneities in surface charge density adds significant functional power to SICM.…”
Section: (A) Surface Charge Mappingmentioning
confidence: 99%
“…We previously reported that the surface charge of liposomes containing cationic lipids was positive, which enhanced their interaction with negatively charged molecules, for example nucleic acids (Endo-Takahashi et al, 2013, 2014. Since bacterial cell surfaces are negatively charged due to the dissociation of a phosphate group and carboxyl group under neutral conditions, biofilms have also been suggested to have a negative charge (Li et al, 2013;Terada et al, 2012).…”
Section: Introductionmentioning
confidence: 97%